Fusarium oxysporum f. sp. radicis‐vanillae is the causal agent of root and stem rot of vanilla. (7th September 2015) - Koyyappurath, S.; Atuahiva, T.; Le Guen, R.; Batina, H.; Le Squin, S.; Gautheron, N.; Edel Hermann, V.; Peribe, J.; Jahiel, M.; Steinberg, C.; Liew, E. C. Y.; Alabouvette, C.; et al.
Abstract : Root and stem rot (RSR) is a very detrimental disease of vanilla worldwide. Fusarium oxysporum is frequently associated with the disease but other Fusarium species are also reported. In this international study, 52 vanilla plots were surveyed in three of the most important vanilla producing countries (Madagascar, Reunion Island and French Polynesia) in order to determine the aetiology of RSR disease. Subsets from the 377 single‐spored Fusarium isolates recovered from rotten roots and stems in the surveys were characterized by molecular genotyping ( EF1α and IGS gene sequences) and pathogenicity assays on Vanilla planifolia and V. ×tahitensis, the two commercially grown vanilla species. Fusarium oxysporum was shown to be the principal species responsible for the disease, representing 79% of the isolates recovered from the RSR tissues, 40% of which induced severe symptoms on inoculated plantlets. Fusarium oxysporum isolates were highly polyphyletic regardless of geographic origin or pathogenicity. Fusarium solani, found in 15% of the samples and inducing only mild symptoms on plantlets, was considered a secondary pathogen of vanilla. Three additional Fusarium species were occasionally isolated in the study ( F. proliferatum, F. concentricum and F. mangiferae ) but were nonpathogenic. Histopathological preparations observed in wide field and multiphoton microscopy showed that F. oxysporum penetrated the root hair region of roots, then invaded the cortical cells where it induced necrosis in both V. planifolia and V. ×tahitensis . The hyphae never invaded the root vascular system up to 9 days post‐inoculation. As a whole, the data demonstrated that RSR of vanilla is present worldwide and that its causal agent should be named F. oxysporum f. sp. radicis‐vanillae .